Surface Metrology Principles for Snow and Ice Friction Studies - Brown, Christopher A. (Frontiers in Mechanical Engineering, 2021)
Explanations of how to apply recent advances in surface metrology science to understanding friction with snow and ice. Conventional surface metrology’s measurement, analyses, and characterizations, have inherent limitations for elucidating tribological interactions. Strong functional correlations and confident discriminations with slider surface topographies, i.e., textures or “roughness”, have largely eluded researchers using conventional height parameters. Building on four decades of research using multiscale methods, two new surface metrology axioms and corollaries are proposed and potential applications of multiscale characterizations and analyses with good potential to provide new technological insights.